Customer satisfaction level toward public hospital’s healthy cafeteria in Sabah / Rafidzah D.K.... [et al.] - D.K., Rafidzah; L., Sonia; A.A., Azizan; R. H., Leoneeta (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Customer satisfaction is influenced by factors such as food quality, service quality and price consequently affected their perception. This study was conducted to determine customer satisfaction level and to identify the difference between demographic profiles. A total of 321 respondents from healthy cafeterias located in public hospital in Kota Kinabalu, Sabah. The tests used are descriptive test, Mann- Whitney U and Kruskal-Wallis. The results show for food quality, various healthy menu items offered scored the highest mean (4.86±1.41) and food temperature based on customer preference scored the lowest mean (4.14±1.58). For service quality, presence of physical facilities scored the highest mean (5.44±1.28) and special routes for patients, senior citizens are provided scored the lowest mean (3.15±1.64) and for last factor which is price, the price is cheaper than nearby food establishments scored the highest mean (4.63±1.54) and price charged for each kind of dish is suitable is scored the lowest mean (4.40±1.57). Between three factor only price has a significant difference (p<0.05) with the demographic factors such as age, race, religion, education level, occupation, monthly income and visiting intentions except gender. In conclusion customers at Healthy Cafeteria take price as a vital factor in assessing their satisfaction level.